Response of Soil Water and Wheat Yield to Rainfall and Temperature Change on the Loess Plateau, China - Xuechun Wang; Muslim Qadir; Fahd Rasul; Guotao Yang; Yungao Hu (Agronomy, 2018)
Understanding the influences of rainfall and temperature on soil water and the grain production of winter wheat (Triticum aestivum L.), is of great importance to ensure the sustainability of food production on the Loess Plateau of China. Based on calibration and evaluation, the Environmental Policy Integrated Climate (EPIC) model was employed to determine the response of soil water and winter wheat to rainfall and temperature changing over the last 30 years in different regions. Results showed that (1) the EPIC model simulated soil water content well in 0–2 m soil, with a relative root mean square error (RRMSE) value of 6.0~14.0%, and the mean value of R2 was 0.824, which was similar to the value of ME (0.815); (2) rainfall decreased 13.6–24.9% more from 2001 to 2010 than it did during 1961–2000, while its minimum and maximum temperature increased 1.00–1.55 °C and 0.30–0.84 °C respectively, in comparison with 1961–2000; (3) both the increase of maximum temperature and the decrease of rainfall were harmful to the production of winter wheat. Contrarily, the increase of minimum temperature was beneficial to the production of winter wheat on the Loess Plateau of China. Furthermore, due to rainfall decreasing, the winter wheat yield of Luochuan, Changwu, Yuncheng, and Yan’an decreased by 8.5%, 7.6%, 11.7%, and 12.3%, respectively. Because of the rising of the maximum temperature, winter wheat yield decreased 6.4%, 6.8%, 7.2%, and −3.0%, respectively. On the other hand, the increase of the minimum temperature raised the winter wheat yield of 8.8%, 10.2%, 1.5%, and 12.0%, respectively. Climate change, either precipitation reduction or temperature increase, decreased soil water in the dry land winter wheat field. Therefore, more water-saving technologies are needed to adapt to climate change, to store and use water sources more effectively in semi-arid regions. Though precipitation reduction and maximum temperature increase produced negative impacts on winter wheat yield, the uptrend in minimum temperature is better for increasing the winter wheat yield, which can be used by farmers and governments to adapt to climate change, by adjusting planting time properly.